Comparison of the reluctance laminated and solid rotor synchronous machine operating at high temperatures. Issue 4 (1st July 2019) - Lefik, Marcin; Komeza, Krzysztof; Napieralska-Juszczak, Ewa; Roger, Daniel; Napieralski, Piotr Andrzej
Abstract : Purpose: The purpose of this paper is to present a comparison between reluctance synchronous machine-enabling work at high internal temperature (HT° machine) with laminated and solid rotor. Design/methodology/approach: To obtain heat sources for the thermal model, calculations of the electromagnetic field were made using the Opera 3D program including effect of rotation and the resulting eddy current losses. To analyse the thermal phenomenon, the 3D coupled thermal-fluid (CFD) model is used. Findings: The presented results show clearly that laminated construction is much better from a point of view of efficiency and temperature. However, solid construction can be interesting for high speed machines due to their mechanical robustness. Research limitations/implications: The main problem, despite the use of parallel calculations, is the long calculation time. Practical implications: The obtained simulation and experimental results show the possibility of building a machine operating at a much higher ambient temperature than it was previously produced for example in the vicinity of the aircraft turbines. Originality/value: The paper presents the application of fully three-dimensional coupled electromagnetic and thermal analysis of new machine constructions designed for elevated temperature.